Did Changes to Disciplinary Segregation Policy Affect Rates of Institutional Misconduct? - McNeeley, Susan M. (Criminal justice and behavior, 2023)
Due to concerns about the harmful effects of restrictive housing, the Minnesota Department of Corrections reduced the maximum disciplinary segregation sentence length from 720 days (about 2 years) to 90 days in September 2016. Then, in response to a perceived increase in violence within the facilities, the policy was changed again in July 2019 to allow for maximum segregation sentences of nearly a year for the most serious offenses. This study employs a quasi-experimental design to empirically test whether and how these changes affected total misconduct, violent misconduct, and incarcerated-person-on-staff assault within Minnesota prisons. The results of interrupted time series analyses showed a moderate, statistically significant initial increase in violent misconduct after the reduction in segregation sentence length in September 2016. There were also statistically significant and larger initial increases in both violent and total misconduct after the July 2019 increase in segregation sentence length for serious infractions.